THE INFLUENCES OF FLASHBACK TO THE PLOT “THE IRON LADY” MOVIE - Thomas Joni Verawanto Aristo (STKIP Persada Khatulistiwa Sintang, 2018)
The aims of th study are (1) to describe the plot arrangement of The Iron Lady and (2) to describe the type of plot in The Iron Lady.In this research, researcher was used descriptive and qualitative technique because this descriptive analysis was based on the data of the movie. The researcher collected the data by watching movie. The technique was conducted as a means to understand the intrinsic elements of the movie especially the plot arrangement and type of the plot of The Iron Lady. A qualitative analysis is a part of primary reasearch. It can be done either by investigating the subject or phenomenon. The qualitative data in this thesis are the intrinsic element of the movie that will be described and discussed in this report.The results of the research were about the plot arrangement and the type of the plot in The iron Lady movie. The plot arrangment consist of three part, they are the beginning, the middle, and the end. Based on the plot arrangement, the middle of the story is more interesting, because of the story present some complicated problems. However the story is still entertaining. Meanwhile the type of the plot of The iron Lady is Flashback. The aspects of the flasback plot are Exposition, Raising Action, Climax, Falling Action, and Catastrophe.Keywords : Plot Arrangement, Flashback, Story